Progress in defining progression in NMIBC - Gierth, Michael; Burger, Maximilian (Nature reviews. Urology, 2013)
The International Bladder Cancer Group has proposed a new definition for disease progression in non-muscle-invasive bladder cancer that includes stage and grade progression. Although this definition will inevitably be subject to changes, it can currently be regarded as the gold standard for future trials, publications and protocols.